Changes of tricuspid valve geometry after interventional implantation of an anuloplasty band. (25th November 2020) - Landendinger, M; Smolka, S; Haug, J; Troebs, M; Ammon, F; Marwan, M; Achenbach, S; Arnold, M
Abstract: Background: Implantation of an anuloplasty band (Cardioband, Edwards Lifesciences) is a new treatment option for patients with functional tricuspid regurgitation (TR). The initial clinical results are promising. Nevertheless very few details about the mechanism of reducing TR beyond the basic principle of reducing the annular perimeter are known. Therefore we sought to study the changes of the tricuspid valve geometry after Cardioband implantation. Methods: In all patients, that were treated by Cardioband implantation for tricuspid valve implantation at our institution, fluoroscopic images of the implant were optained at an angle, which would correspond to an echocardiographic "enface" view of the tricuspid valve. In these images the area enclosed by the implant, the perimeter of this area, the septal to lateral diameter, the anterior to posterior diameter and the length of the implant before and after contracting the band was measured. In all patients an echocardiographic evaluation of the tricuspid regurgitation before and after cardioband implantation was performed. These clinical finding were correlated to changes of the above mentioned dimension in the fluoroscopic images. Results: Between October 2018 und January 2019 17 patients with severe tricuspid regurgitation were treated by Cardioband implantation. In one patient the procedure had to be aborted due to extensive movement of the tricuspid annulus. In the remaining 16 patients (mean age 78±8 years, 7 males) the procedure could be completed successfully and the required measurements were done. The mean severity grade (5 grade scale) of the TR was 3.5±0.6 before and 2±0.7 (p<0.0001) after the implantation, the corresponding mean vena contracta changed from 12±4 mm to 6±3 mm (p<0.000, 51% reduction). The area decreased after band contraction from 10.6±1.4 cm 2 to 4.7±1.4 cm 2 (p<0.0001; 56% reduction), the perimeter from 13.4±1.8 cm to 9.6±1.6 cm (p<0.0001; 28% reduction) the septal to lateral diameter from 2.8±0.5 cm to 1.6±0.2 cm (p<0.0001; 40% reduction), the anterior to posterior diameter from 4.8±0.9 cm to 3.8±1.0 cm (p<0.005; 19% reduction) and the measured device length from 8.6 cm±1.0 to 5.8±0.8 cm (p<0.0001; 32% reduction). The strongest correlation was seen between area reduction and reduction of the vena contracta (r=0.5), reduction of the septal to lateral dimension as well as the reduction of the device length had a weaker correlation (r=0.3 and r=0.2). The reduction of the anterior posterior diameter and perimeter reduction showed no relevant correlation with regard to TR reduction. Conclusion: In our patient population Cardioband implantation lead to effective TR reduction. Area reduction and reduction of the septal to lateral diameter of the tricuspid valve seem to have the strongest impact. These findings may be considered when implantations techniques are being optimized or when new devices for TR treatment are developed. Funding Acknowledgement: Type of funding source: None